Selected university and college-based campus theatres in Iloilo City during the Martial Law period. - Pallon, Marie Andre L
This is a historico-descriptive study on the development of selected university and college-based campus theatre in Iloilo City during the Martial Law period. Its specific objective are to trace the origin and development of Ilonggo theatre from pre-colonial to the pre-Martial Law period; To identify and describe the different features of selected university and college-based campus theatre in Iloilo City during the Martial Law period as to the type of production, production themes, directors, performers, costumes, lights and sounds, venues, performing groups, production costs and entrance fees; To identify and describe the problems encountered by campus theatre in Iloilo City as well as their solutions during the Martial Law period and to establish the significance of campus theatre on the lives of the Ilonggos during the Martial Law period. (p)The researcher primarily employed oral history method in gathering information from the field. Interview guide was used as a dat-gathering instrument. Informants were chosn based on their individual participation in university and college campus theatre groups and as active members of the Iloilo Drama Association. Moreover, the researcher also gathered from informant's pictures, playbills, news clips for supplementary purposes. (p)Theatre existed in Iloilo City before the coming of the colonizers. It was manifested in the actions performed by the native babaylan, the spritual leader of the tribe. The babaylan was the one provided the mood, setting, dance and music of the performance. The movements were performed in a form of a ritual during different occasions such as marriage, baptism, death, hunting and many more. Formal theatre was not yet established but its elements were already present. Themes of the Hiligaynon zarzuela during the Amrican occupation were full of social consciousness and antionalist ideas during the Japanese occupation Ilonggo theatre never flourished. (p)In the 1960's Ilonggo theatre was popular in the different campuses in Iloilo City. Faculties from selected universities and colleges in Iloilo City gathered to organize a drama group in 1968. The Iloilo Drama Association was born through the efforts of Fr. Eduardo Perez, O.S.A. from the University of San Agustin. The political situation during the Martial Law period changed the lives of amny Ilonggos. Freedom of expression was curtailed. Several production types were produced during the Martial law years in Iloilo City such as straight dramas, dance dramas, theatre of the absurd, chamber theatre, children's theatre and Broadway musical plays. Most themes of the play presented apolitical messages. (p)There were several performing groups such as Teatro CPU, USA Litte Theatre, UI Performing Arts - Teatro Busilak, UP Theatre Arts Club, UP Teatro Amakan, Theatre Arts Guild of UP Colleges Iloilo (TAGUPCI) and WVSU Little Theatre. Production cost varied in every performance depending on the types of production and scripts. (p)Money was a problem encountered by campus theatre in Iloilo City. There was no support from the school administration to produce a play. Performers and advisers invested personal money, which was refunded by income from the netrance fee. lack of better materials for play production and rehearsal schedules were problems too. Researhers were conducted for improvement of productions and schedules were held during weekends in some selected places. (p)Campus theatre affected the lives of many Ilonggos during the Martial Law years. The plays helped the audience to have a feeling of relief from anxiety during hard times. It also gave an opportunity for the Ilonggo performers to release tension brought about by unstable political situations, through acting on stage. Moreover, campus theatre developed among the citizens of Iloilo, the love for theatre arts and likewise deepened their enthusiam in the field of performing arts. (p)The performers of the play developed their individual talents. Expressing themselves to the audience led to pouring out of innate emotions, which helped them to act impressively. The production of the plays was the one, which strenghtened the camaraderie and relationship of the group. All plays have noral lessons. The play taught the Ilonggo performers to be creative and resourceful. Many individuals or groups tried to sponsor popular plays. They were the ones who sold tickets. The audience empathized with the situation of the play, and realized the same oppression made by the Martial Law regime on the Filipinos. Plays were used as an eye opener of Philippine social realities.